PROPERTIES OF MINERAL POWDER AND THEIR EFFECT ON ASPHALT-CONCRETE MIXTURES - Urishbayev , Elbek Elmurod o‘g‘li (Innovative Development in Educational Activities, 2024)
In this article the physical and mechanical properties of the asphalt concrete mixes according to the current standards the mineral powder added to the mixture at certain percentages and information on the results of the influence of the asphalt mix on the technical parametrs.